Deep Learning Approach in Inclusive Islamic Education for Children with Special Needs (Lembaga Pengembangan Kinerja Dosen, 2025)
This article explores the application of the Deep Learning approach in inclusive Islamic Religious Education (PAI) for children with special needs (ABK), with a focus on improving the understanding of abstract concepts such as monotheism and morals. The main problems faced by ABK in PAI learning include difficulties in understanding religious concepts due to cognitive, emotional, and sensory challenges. The purpose of this study is to analyze the urgency of Deep Learning in improving the spiritual understanding, motivation, and well-being of ABK through more personalized and reflective learning. The methods used include reflective strategies such as journals and discussions, adaptive media in the form of animation and audio, and collaborative learning with peers. The findings show that the application of Deep Learning improves ABK's in-depth understanding of religious values, as well as spiritual motivation and the ability to apply ethics in everyday life. The conclusion of this study is that Deep Learning can be an effective solution in inclusive PAI learning, supporting teachers in developing more humanistic learning designs and focusing on the character building of ABK.